Thinking Styles in College Students from Buenos Aires - Freiberg Hoffmann, Agustín (2020)
Different academic situations demand the use of specific thinking styles in order to achieve success in higher educational. The study aims to describe college students’ thinking styles and to relate them with academic achievement. The sample was composed of 225 college students representing diverse majors. A MANCOVA test revealed significant multivariate effects for sex and major, as well as for the interaction between sex and working status. Correlational analysis verified significant associations between academic achievement and styles for Social and Human Science majors. Results are discussed from theoretical and practical standpoints.